Exploring a role for Chemerin in the cardiovascular and musculoskeletal benefits of intradialytic exercise in the hemodialysis population - Mingyue Deng; Daniel S. March; Darren R. Churchwood; Hannah M. L. Young; Patrick J. Highton; Matthew J. Denniff; Matthew P. M. Graham-Brown; James O. Burton; Luke A. Baker (PLoS ONE, 2025)
Background Cardiovascular disease is the leading cause of death for people receiving hemodialysis. Intradialytic cycling (IDC) has been shown to improve cardiovascular health in the hemodialysis population, but specific mechanisms require elucidation. Chemerin is an adipokine which contributes to the inflammatory process and may be associated with the cardiovascular benefits of IDC and physical function in hemodialysis population. Methods Adults undertaking ≥3 months hemodialysis were randomized to either IDC (30 min each time, moderate intensity, thrice weekly) and usual care; or usual care only (control group). 88 blood samples were retrospectively analyzed for chemerin concentrations using ELISA. Unadjusted and adjusted linear regression was used to understand how changes in chemerin are associated with changes in cardiovascular and musculoskeletal health in response to IDC. Results There was a significant increase of plasma chemerin concentration after 6 months in both groups. A positive association was detected between chemerin and short physical performance battery at baseline (β = 0.264, p = 0.017). There was no correlation of chemerin with cardiovascular, body composition, and other physical function markers. Conclusions This study is the first to show plasma level of chemerin increases with time on hemodialysis. No evidence was found to support a role for chemerin in modifying cardiac structure and function in people undertaking IDC. Further studies should investigate the associations between chemerin and physical performance.